EXECUTORSHIP REPORTING–SOME HISTORICAL NOTES. - Hay, Leon E. (The Accounting Review, 1961)
Abstract This article focuses on some historical notes on executorship reporting. For almost eight centuries before 1857 the distribution of real property of a decedent had been under the jurisdiction of civil courts. The decedent's wishes as to the disposition of his real property were expressed in a document called a "will." Executors in England during most of the eight-century period under discussion seem, in general, to have prepared their accounts in narrative form. Two fifteenth century executors' statements are particularly interesting as examples of the evolution of reporting technique. The first, that of the estate of Bishop Skirlaw, who died in 1406, presents the inventory and report in narrative form with no clear separation between the two documents. No money columns are used, nor is there much grouping of like items, although the late bishop had been immensely wealthy and left a long will full of detailed directions as to the duties of the executors. Accounting histories say that double entry bookkeeping was introduced into England in the sixteenth century and the preparation of statements from ledger accounts was introduced in the seventeenth century.